Tajikistan’s agrifood system: The past performance and future opportunities and challenges - Diao, Xinshen; Khakimov, Parviz; Ashurov, Timur; Aliev, Jovidon; Fang, Peixun; Randriamamonjy, Josee; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2025)
This study analyzes the past performance and future opportunities and challenges of Tajikistan’s agrifood system (AFS). The study measures the current size and structure of AFS and its historical contribution to economic growth and transformation through a data-driven exercise. A forward-looking economywide model is used to assess the effectiveness of future AFS growth (led by agricultural productivity gains in different value chains) in promoting multiple development outcomes. The findings of the study indicate that AFS transformation is an important part of Tajikistan’s economic transformation and structural change. Because of lower growth contributions from AFS’s off-farm components as well as fewer farm workers moving from primary agriculture to off-farm activities within AFS, Tajikistan’s AFS did not grow as quickly as the broader economy. Expanding off-farm activities to boost on-farm productivity growth remains a challenge for sustainable transformation of Tajikistan’s AFS. Using an economywide model, we find that there is no single value chain group that would most effectively achieve all desired development outcomes including broad economic growth, job creation, declining poverty, and improved diets. Livestock value chains, however, have the most potential to contribute to multiple development outcomes, particularly to dietary improvement, and these value chains also performed impressively during the study period. Moreover, most cattle and ruminants are owned by household farms, and their growth could contribute to broader agricultural transformation. The maize value chain also ranks high in the model-based comparison, but it seems to only modestly contribute to job creation and diet quality and had performed disappointingly during the study period. While growth in livestock and maize value chains face a series of challenges and constraints, promoting them together seems to offer an effective way to broadly achieve important development outcomes.